Tick-Borne Encephalitis Virus Habitats in North East Germany: Reemergence of TBEV in Ticks after 15 Years of Inactivity. (7th July 2014) - Frimmel, Silvius; Krienke, Anja; Riebold, Diana; Loebermann, Micha; Littmann, Martina; Fiedler, Karin; Klaus, Christine; Süss, Jochen; Reisinger, Emil Christian
Abstract : The incidence of tick-borne encephalitis has risen in Europe since 1990 and the tick-borne encephalitis virus (TBEV) has been documented to be spreading into regions where it was not previously endemic. In Mecklenburg-West Pomerania, a federal state in Northern Germany, TBEV was not detectable in over 16, 000 collected ticks between 1992 and 2004. Until 2004, the last human case of TBE in the region was reported in 1985. Following the occurrence of three autochthonous human cases of TBE after 2004, however, we collected ticks from the areas in which the infections were contracted. To increase the chance of detecting TBEV-RNA, some of the ticks were fed on mice. Using nested RT-PCR, we were able to confirm the presence of TBEV in ticks for the first time after 15 years. A phylogenetic analysis revealed a close relationship between the sequences we obtained and a TBEV sequence from Mecklenburg-East Pomerania published in 1992 and pointed to the reemergence of a natural focus of TBEV after years of low activity. Our results imply that natural foci of TBEV may either persist at low levels of activity for years or reemerge through the agency of migrating birds.